TITLES OF LIS TEXTBOOKS AND RESEARCH ARTICLES: A BIBLIOMETRIC STUDY - Kaur, Kiran; Lee, Lily; Tiew, Wai Sin; Sen, B. K. (Malaysian Journal of Library and Information Science, 1997)
Studies the number of keywords in the titles of library and information science textbooks and research articles. Results indicate that on an average the number of keywords in the titles of research articles and textbooks are 7.7 and 5 respectively and prove the hypothesis that the number of keywords in textbook titles is less than that of the research article titles.